2021
DOI: 10.1002/med.21799
|View full text |Cite
|
Sign up to set email alerts
|

MALT1 as a promising target to treat lymphoma and other diseases related to MALT1 anomalies

Abstract: Mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT1) is a key adaptor protein that regulates the NF‐κB pathway, in which MALT1 functions as a scaffold protein and protease to trigger downstream signals. The abnormal expression of MALT1 is closely associated with lymphomagenesis and other diseases, including solid tumors and autoimmune diseases. MALT1 is the only protease in the underlying pathogenesis of these diseases, and its proteolytic activity can be pharmacologically regulated. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 146 publications
(249 reference statements)
0
13
0
Order By: Relevance
“…We then evaluated the in vitro MALT1 inhibition effect for all synthesized derivatives. Thioridazine, a reported noncovalent selective MALT1 inhibitor, was used as the positive control. ,, As summarized in Table , we first investigated the inhibition effect of the structure skeleton with different substituents on MALT1 protease activity. Compound 14a , the structure skeleton with a hydrogen atom substituent, showed a weak in vitro MALT1 inhibition with the IC 50 value over 25 μM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then evaluated the in vitro MALT1 inhibition effect for all synthesized derivatives. Thioridazine, a reported noncovalent selective MALT1 inhibitor, was used as the positive control. ,, As summarized in Table , we first investigated the inhibition effect of the structure skeleton with different substituents on MALT1 protease activity. Compound 14a , the structure skeleton with a hydrogen atom substituent, showed a weak in vitro MALT1 inhibition with the IC 50 value over 25 μM.…”
Section: Resultsmentioning
confidence: 99%
“…However, there have been few research and development cases of MALT1 inhibitors so far. 31 Therefore, the development of MALT1 inhibitors is urgent for the treatment of lymphoma. Herein, we identified and designed a novel class of potent 5-oxo-1-thioxo-4,5-dihydro-1H-thiazolo-[3,4-a]quinazoline-based MALT1 inhibitors and their covalent derivatives and demonstrated their excellent antitumor effects on ABC-DLBCL cells.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1) is a unique paracaspase and key component of the CARD11/MALT1/BCL10 complex that mediates NF-κB signalling [ 120 , 121 ]. When dysregulated, MALT1 acts as a proto-oncogene and is known to contribute to tumorigenesis in lymphoid malignancies, including a prominent role in MALT lymphoma and activated B-cell type DLBCL [ 122 ].…”
Section: Review Of Approved Small Molecule Inhibitorsmentioning
confidence: 99%
“…Three main classes of MALT1 inhibitors are in development: allosteric, covalent and protein degraders [ 121 , 123 ]. Pre-clinical studies have demonstrated in vivo and in vitro suppression of the growth of the ABC-DLBCL cell [ 123 , 124 , 125 ].…”
Section: Review Of Approved Small Molecule Inhibitorsmentioning
confidence: 99%